2015
DOI: 10.1039/c5fo00301f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of high stability fucoxanthin on palmitic acid-induced lipid accumulation in human adipose-derived stem cells through modulation of long non-coding RNA

Abstract: Obesity is a serious worldwide disease, which is growing in epidemic proportions. Adipose-derived stem cells (ADSCs) are characterized as a source of mesenchymal stem cells that have acted as a potential application for regeneration. Recently, seaweeds rich in flavonoids and polysaccharides have been supposed to show the ability to modulate risk factors for obesity and related diseases. In the present study, we investigated the anti-obesity properties of high stability fucoxanthin (HS-Fx) derived from brown se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Moreover, we were the first to use fucoxanthin on an intestinal inflammatory model. We also observed that LMF+HS-Fucox (99.34±3.94%) showed a stronger effect on increasing cell viability than LMF (94.56±3.26%) and HS-Fucox (91.33±7.99%) at 100 µg/ml, a result that matched our previous studies showing that HS-Fucox may efficiently scavenge reactive-oxygen species (ROS) ( 38 ) and that LMF reduced inflammation through the inhibition of NF-κB ( 39 ). Under the co-culture of Caco-2 cells and samples, cell viability showed no significant effect with or without B. lactis ( Fig.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, we were the first to use fucoxanthin on an intestinal inflammatory model. We also observed that LMF+HS-Fucox (99.34±3.94%) showed a stronger effect on increasing cell viability than LMF (94.56±3.26%) and HS-Fucox (91.33±7.99%) at 100 µg/ml, a result that matched our previous studies showing that HS-Fucox may efficiently scavenge reactive-oxygen species (ROS) ( 38 ) and that LMF reduced inflammation through the inhibition of NF-κB ( 39 ). Under the co-culture of Caco-2 cells and samples, cell viability showed no significant effect with or without B. lactis ( Fig.…”
Section: Resultssupporting
confidence: 88%
“…For comparison, by adding LMF with LPS treatment, the increasing trend of TER and tight junction protein expressions was only slightly higher than that of the HS-Fucox group. This result indicated that LMF and HS-Fucox exhibited a protective effect on epithelial cell injury, and HS-Fucox offered scavenging ROS activity ( 38 ) strong enough to make LMF+HS-Fucox an appropriate therapy for the treatment of inflammatory bowel diseases.…”
Section: Resultsmentioning
confidence: 92%
“…Accumulated evidences suggested that lncRNAs function as the responder for stimulus from drugs and crucially regulate disease progresses by association with its downstream signaling pathway (Tang et al, ; Lin et al, ). Our present study defined lncRNA‐MALAT1 as a key regulator in mediating cardio‐protective effects of fentanyl against I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antiadipogenic effects in culture, biochanin A was also found to inhibit the expression of proinflammatory cytokines (S. J. Su et al, ). Other botanical compounds such as high‐stability fucoxanthin from brown seaweed and the flavonoid 3,4′‐dihydroxyflavone modulate adipogenesis and metabolism in cultured ASCs through their antioxidant properties (Han et al, ; W. C. Lin et al, ). However, none of the abovementioned compounds have been examined for their effects on ASC biology in vivo.…”
Section: Overview Of Recently Published Work In Ascsmentioning
confidence: 99%